Analisis Dampak Rasio Profitabilitas dan Rasio Solvabilitas terhadap Harga Saham pada Sub Sektor Jasa Asuransi - Umi Rahma Dhany; Muhammad Rizki Yusuf; Joni Hendra (Ecobuss, 2021)
This study has several objectives, namely to determine the simultaneous, partial and dominant influence between the variables of return on assets (ROA), return on equity (ROE), and debt to equity ratio (DER) on stock prices in insurance service sub-sector companies that listed on the Indonesia Stock Exchange. This type of research is associative quantitative research and data collection methods using documentation studies and literature studies. The sampling technique used purposive sampling by taking a sample of 5 years with 10 companies. The results showed that the independent variables had a simultaneous effect on profitability. The t-test shows that the ROA variable has a partial effect on Stock Prices and the ROE variable has a partial effect on Stock Prices and also the DER variable has a partial effect on Stock Prices.